2022
DOI: 10.1098/rspa.2022.0149
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of tension-induced film wrinkling and restabilization: a review

Abstract: Wrinkling of thin films under tension is omnipresent in nature and modern industry, a phenomenon which has aroused considerable attention during the past two decades because of its intricate nonlinear behaviours and intriguing morphology changes. Here, we review recent advancements in the mechanics of tension-induced film wrinkling and restabilization, by identifying three major stages of its progress: small-strain (less than 5 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 116 publications
(213 reference statements)
1
14
0
Order By: Relevance
“…Currently considerable studies have been performed on stretch-induced wrinkling in thin elastic sheets. 16 This problem is in contrast to conventional buckling in that it is accompanied by extensive stretching. 17 An earlier approach to characterizing the wrinkled regions in thin sheets is the tension-field theory devised by Wagner 18 and further improved by Pipkin 19 and Steigmann.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently considerable studies have been performed on stretch-induced wrinkling in thin elastic sheets. 16 This problem is in contrast to conventional buckling in that it is accompanied by extensive stretching. 17 An earlier approach to characterizing the wrinkled regions in thin sheets is the tension-field theory devised by Wagner 18 and further improved by Pipkin 19 and Steigmann.…”
Section: Introductionmentioning
confidence: 99%
“…Currently considerable studies have been performed on stretch‐induced wrinkling in thin elastic sheets 16 . This problem is in contrast to conventional buckling in that it is accompanied by extensive stretching 17 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 27 ] This results in structural instability due to tensile loading and results in local surface wave formations. [ 28 ] Furthermore, Su et al. showed that the thickness–width ratio affects buckling.…”
Section: Introductionmentioning
confidence: 99%
“…[27] This results in structural instability due to tensile loading and results in local surface wave formations. [28] Furthermore, Su et al showed that the thickness-width ratio affects buckling. Below one, they show ultra-thin films wrinkles for samples' thickness smaller than 1 µm, and with increasing the thickness, they reported buckling and scissoring regions.…”
Section: Introductionmentioning
confidence: 99%
“…Thin shells are one of the most widely used structural elements in civil [1], mechanical [2,3], architectural [4], biomedical [5,6], aeronautical [7] and aerospace [8,9] applications because they enable complex and large shapes while maintaining minimal weight. The limited thickness requires a careful characterization and modelling of the behaviour of shell structures, to thoroughly assess the stress distribution and avoid structural failure [10][11][12][13]. Although the stresses in statically determinate thin shell configurations can be analytically obtained from equilibrium equations in most of the cases [14], complex non-axisymmetric and statically indeterminate shapes require numerical analyses that necessitate the material constitutive model for an accurate prediction of the mechanical behaviour.…”
Section: Introductionmentioning
confidence: 99%